2021
DOI: 10.3390/children8070603
|View full text |Cite
|
Sign up to set email alerts
|

ArtiSential® Articulated Wrist-Like Instruments and Their First Application in Pediatric Minimally Invasive Surgery: Case Reports and Literature Review of the Most Commonly Available Robot-Inspired Devices

Abstract: Background: Robotic surgery is currently a reality in surgical practice, and many endeavors have been made to extend its application also in pediatric surgery. In the absence of easy access to a robotic surgical system, new devices have been developed to offer a valid alternative such as wristed instruments. These differ from conventional laparoscopic instruments owing to a wrist-like mechanism at the tip, which faithfully reproduces the movements of the surgeon’s hands, regaining more movement’s degrees; Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…[12][13][14] Their applications have also been observed in pediatric, cardiovascular, and thoracic surgeries. [15][16][17][18] In accordance with earlier studies, we found that articulated instruments could be managed almost identically to surgical robots during TMEs, leading to negligible differences between the two approaches.…”
Section: Discussionsupporting
confidence: 91%
“…[12][13][14] Their applications have also been observed in pediatric, cardiovascular, and thoracic surgeries. [15][16][17][18] In accordance with earlier studies, we found that articulated instruments could be managed almost identically to surgical robots during TMEs, leading to negligible differences between the two approaches.…”
Section: Discussionsupporting
confidence: 91%
“…Thus current evidence shows that the use of articulating instruments in laparoscopic gastrectomy does not increase postoperative morbidity. With the start of these studies in laparoscopic gastrectomy, reports of the use of this device in other types of surgery such as colorectal [9][10][11], gynecological [12], and pediatric surgery [13] are increasing.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, current evidence shows that the use of articulating instruments in laparoscopic gastrectomy does not increase postoperative morbidity. With laparoscopic gastrectomy as a start, reports of the use of this device in other types of surgery such as colorectal 10 12 , gynecological 13 , and pediatric surgery 14 are increasing.…”
Section: Discussionmentioning
confidence: 99%